Kajian Teknis Produktivitas Alat Gali Muat Dan Alat Angkut Di PT Jaga Aman Sarana Jobsite PT Koninis Fajar Mineral Kabupaten Banggai - Mahardika, Yudi; Ag. Isjudarto; Novandri Kusuma Wardana (ReTII, 2023)
Jaga Aman Sarana is a contractor company engaged in Nickel mining. The mining location is located in Tuntung Village, Bunta District, Banggai Regency, Central Sulawesi Province. Mining is carried out using an open pit system (Surface mining), the mechanical equipment used in this company is 1 unit of excavator and 5 units of dump trucks. The formulation of the problem in this study is that the ore production target set by the company has not been achieved, which is 154,626 wmt/month and the occurrence of obstacles at PT. Safeguard the Facilities. so, a technical study of the productivity of the digging and hauling equipment is carried out so that the production targets set by the company can be achieved. The actual production obtained by the fleet for loading and unloading equipment is 35,341 wmt/month and for conveyances is 35,310 wmt/month, where the current production target has not been achieved. Efforts to increase production targets are carried out by improving the cycle time of digging and hauling equipment and improving work efficiency. As for the calculations after carrying out the repairs, the production of repairs obtained in the fleet for digging equipment is 182.093 wmt/month and for conveyances is 156.235 wmt/month. Thus, the production target set can be achieved.